A61 FOCUSING ON THE FUTURE: REDUCING BARRIERS AND IMPROVING ACCESS TO IBD SPECIALTY CARE ACROSS CANADA. (26th February 2020) - Heisler, C; Mirza, R; Kits, O; Zelinsky, S; Veldhuyzen van Zanten, S; Nguyen, G C; MacMillan, M A; Lakatos, P L; Targownik, L; Fowler, S; Rioux, K P; Jones, J
Abstract: Background: Canada has the highest global age-adjusted incidence and prevalence rates of Inflammatory Bowel Disease (IBD). Resulting from compounding prevalence and limited resources, timely access to specialty care is a challenge faced by patients and healthcare providers. Despite this issue, there has been no published research elucidating the patient perspective using qualitative approaches to compare and contrast the patient experience across Canada. Aims: To elicit a qualitative data stream to better understand phenomena related to access to healthcare for Canadians living with IBD from a patient-centered perspective. Methods: Patients diagnosed with IBD (≥18 years of age) were recruited from gastroenterology clinics and communities through IBD specialists and Crohn's & Colitis Canada. To ensure geographic diversity and representation, patients were recruited from urban and rural regions. In order to acquire multiple access perspectives, patients were invited to bring a family member who was involved in their care to the focus groups. Co-facilitated by a researcher and a patient research partner, the focus groups were held in Nova Scotia, New Brunswick, Quebec, Ontario, Manitoba, Saskatchewan, and British Columbia. All focus groups were audio recorded, transcribed, and coded for themes. Themes were distilled through qualitative thematic analysis using Atlas.ti software to ascertain congruence or discordance of IBD specialty care access experiences. Results: A total of 63 participants were recruited in fourteen focus groups across seven provinces. The majority of participants were female (41/63, 65%) and from urban/suburban regions (34/63, 54%). The mean age of participants was 48 years (SD=16 years, range=16 to 77 years). Preliminary analyses illustrated three patient-identified access barrier themes: 1) Lack of multidisciplinary care (psycho-social and nutrition support), 2) Diagnostic delay, and 3) Inability to effectively receive and provide communication with healthcare providers. In response, four solutions were proposed: 1) Integration of holistic care into the clinical practice, 2) Readily accessible psycho-social and nutritional support, 3) Increased patient advocacy, and 4) Continuity and liaison through provision of a healthcare navigator resource. Conclusions: The complexity of specialty care access for IBD patients in Canada cannot be underestimated. It is vital to possess a robust understanding of healthcare system structures, processes, and the significant impact these factors have on patients and the care received. Through the use of patient-centered exploration of barriers and facilitators, access to IBD specialty care in Canada can be better understood and improved on both a provincial and national scale. Funding Agencies: CIHRNova Scotia Health Authority Research Fund